Reliabilitas Undang-Undang Ekstradisi (Tinjauan Yuridis Terhadap Ekstradisi) - Nanda Clarissa Maria Manek (Universitas Widya Gama Malang, 2022)
Human needs are evolving as time goes by. Some of the people chose to strugle to fill their everyday needs, while some of them chose the shortcut to get what they want. Like a shadow behind the light, crimes never disappear from social life. Many individuals as well as the peoples chose to commit crime as long as they get what they need and what they want. These things triggers the numbers of crimes. More perperators take advantage of every chance or loopholes in the laws, to evade punishment which will be given to them related to their comitted crime. Law paragraph 1 Year 1979 about extradition applied to arrest and adjudicate the perperators which on purpose looking for safety on crimes they commited by running to another country. However, on the embodiment, this extradition process takes so much time even can be turn down by the requested country, and the perperator can still enjoy their freedom as long as this extradition process takes place. This research using normative juridical method, where will discuss about constituent, principle, and the extradition process which regulated in Law Paragraph 1 Year 1979 about extradition, then will be compared with United Nations Convention Against Transnational Organized Crime or commonly reffered as Palermo Convention 2000.